Sexual perceptions among people aged 45 years, association of reproductive health and socio-demographic factors in Klang Valley, Malaysia. - Abd Latiff, Latiffah; Parichehr, Hanachi (Tehran University of Medical Sciences, 2008)
Objective: The objective of this research was to study the sexual perception and practices among people aged 45 years and above and the associated socio-demographic factors.